Interval of detectability of predator DNA after livestock (and wild animal) predation. Issue 1 (December 2019) - Modrow, Jan-Hendrik; Schwark, Thorsten; Nuss, Niklas; Meyer, Nele; Hempel, Jamie; von Wurmb-Schwark, Nicole
Abstract: With the return of the wolf, predation of livestock such as sheep, cattle, and horses, has vastly increased in Europe. DNA swabs are routinely taken from killed animals to clarify whether the predator was a wolf, and to further individualize the animal. However, based on the publication of a German working group, in some cases the – from a forensic point of view doubtful – opinion prevails that securing evidence is no longer promising after 24 or 48 h at the latest. Traces are then not secured, sometimes causing considerable financial loss for the owners of the predated animal(s). To verify the results of the aforementioned study, we conducted an experiment simulating the circumstances after livestock predation. Sheep extremities provided by a local butcher were chewed on by a dog and, after 30 min, were laid out in the woods. After defined intervals, swabs were taken from the limbs, and genetic analyses to detect Canidae specific DNA were performed. Our study shows that successful DNA typing is feasible for at least 72 h after predation. DNA sampling in cases of animals presumably killed by a wolf should thus not be based on the PMI alone, but should be treated individually regarding all circumstances.